A Summing Up - Samuelson, Paul A. (Quarterly Journal of Economics, 1966)
I. The simplest Austrian and more general models, 568. — II. Why reswitching can occur, 571. — III. Reswitching in a durable-machine model, 573. — IV. The well-behaved factor-price frontier, 574. — V. Unconventional relation of total product and interest, 576. — VI. Unconventional capital/output ratios, 577. — VII. Reverse capital deepening and denial of diminishing returns, 579. — VIII. Conclusion, 582.